2013
DOI: 10.4028/www.scientific.net/amm.295-298.210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on Microorganisms Quantity and Soil Physicochemical Property in Rhizosphere of Spinach (<i>Spinacia oleracea</i> L.)

Abstract: To investigate the effects of biochar on greenhouse soil, three biochar treatments, i.e. 0 t ha-1 (C0), 12.5 t ha-1 (C1) and 25 t ha-1 (C2), were applied to the rhizosphere of spinach (Spinacia oleracea L.). And the microbial biomass C (MBC), the quantities of the bacteria, fungi, actinomyces, ammonifying bacteria, azotobacter and denitrifying bacteria, pH, oxidation-reduction potential (Eh), and mineral nutrient content were studied. The results indicated that MBC contents with C2 and C1 treatments were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…It has been reported that the nutrient elements introduced from biochar to the soil promote the growth of ammonifying bacteria, significantly improving the ammonification function of the soil. 49 Nelissen et al 50 reported that biochar can promote the growth of nitrifying bacteria in the soil and accelerate the transformation of NH 4 + −N into NO 3 − −N, thus improving soil nitrification. In the present study, SEM for ryegrass showed that plant roots can improve EMF directly and indirectly through trace elements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the nutrient elements introduced from biochar to the soil promote the growth of ammonifying bacteria, significantly improving the ammonification function of the soil. 49 Nelissen et al 50 reported that biochar can promote the growth of nitrifying bacteria in the soil and accelerate the transformation of NH 4 + −N into NO 3 − −N, thus improving soil nitrification. In the present study, SEM for ryegrass showed that plant roots can improve EMF directly and indirectly through trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of soil EMF may be due to the growth of microorganisms in the rhizosphere soil. 49 The addition of biological carbon into the soil weakened the direct positive effect of the root system on EMF. This result may be because biochar and its chemical reactions in the soil environment generate substances that are harmful to certain microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, biochar amendments in pot and field tests significantly improved the soil pH value and organic matter contents (OMC), hydrolyzable alkali nitrogen, phosphorus, potassium, exchangeable calcium, exchangeable magnesium, zinc, available boron and CEC. Many pot tests have found similar findings and analyzed the related reasons ( Kimetu and Lehmann, 2010 ; Gao et al., 2012 ; Han et al., 2012 ; Zhang et al., 2013a ; Zhang et al., 2013c ; Zhao et al., 2015 ; Zhu et al., 2015 ). However, there is not a complete design for the optimal amount of biochar.…”
Section: Discussionmentioning
confidence: 84%